2021
DOI: 10.3389/fimmu.2021.651709
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Unbalanced Meat Consumption in the First Year of Life Increases Asthma Risk in the PASTURE and LUKAS2 Birth Cohorts

Abstract: A higher diversity of food items introduced in the first year of life has been inversely related to subsequent development of asthma. In the current analysis, we applied latent class analysis (LCA) to systematically assess feeding patterns and to relate them to asthma risk at school age. PASTURE (N=1133) and LUKAS2 (N=228) are prospective birth cohort studies designed to evaluate protective and risk factors for atopic diseases, including dietary patterns. Feeding practices were reported by parents in monthly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…We found a significant increase in the mean proportion of Acinetobacter after 1 year in the control group. A previous study that investigated food introduced in the first year of life and subsequent asthma development showed that unbalanced meat consumption fostered growth of iron scavenging bacteria, such as Acinetobacter , which was related to asthma [ 39 ]. However, the biological mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We found a significant increase in the mean proportion of Acinetobacter after 1 year in the control group. A previous study that investigated food introduced in the first year of life and subsequent asthma development showed that unbalanced meat consumption fostered growth of iron scavenging bacteria, such as Acinetobacter , which was related to asthma [ 39 ]. However, the biological mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Also Yu et al report OR of 1.27 within Chinese children [ 24 ]. Moreover, it was found elevated risk of asthma at age 6 within children consuming meat at the first year of live by an OR of 8.47 [ 25 ]. Previously, a study concluded that an introduction of milk other than breast milk during the first 6 months after birth increased almost two fold the risk of development of persistent asthma [Adjusted Relative Risk (ARR): 1.71] [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of bias in randomized controlled trial (RCT) studies was assessed using the Cochrane Collaboration Risk of Bias tool [ 21 ], and the risk of bias in non-RCT trials was assessed using the Risk of Bias in Nonrandomized Studies of Interventions tool [ 22 ]. For all study reports, the summary Tables ( Supplemental Tables 1 and 2 ) [ [8] , [9] , [10] , [11] , [13] , [14] , [15] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] ,…”
Section: Methodsmentioning
confidence: 99%